Effects of stubborn decision-makers on vaccination and disease propagation in social networks. (2016) - Fukuda, Eriko; Tanimoto, Jun
In this study, we investigate how the presence of 'stubborn' individuals affects other individuals' vaccination behaviour with regard to the spread of infectious disease in a lattice populations and a Barabási-Albert scale-free network. (In this context, 'stubborn' individuals are those who are intransigent about their own vaccination strategy). To meet this research objective, we develop a combined model that is constructed from epidemiological and vaccination dynamics and is based on adaptive imitation behaviour. With regard to preventing disease propagation, the stubborn vaccinated individuals act as 'good role models', as they always take vaccines, whereas the stubborn unvaccinated individuals, in contrast, act as 'bad role models', as they always refuse vaccines. As a result, which stubborn individuals are more influential among the full population in terms of voluntary vaccination behaviour depends not only on their proportion within the population, but also the network structure and the cost of vaccination.